Neurological manifestations of multisystem inflammatory syndrome in children associated with COVID-19 in a tertiary care centre - Chintha, Lakshman; Magar, Suvarna; Vaidya, Varsha; Bhartiya, Shirish; Mehta, Krishna (International Journal of Contemporary Pediatrics, 2023)
Multisystem inflammatory syndrome in children (MIS-C) and adolescents temporally related to COVID-19” is a new entity characterized by fever, multisystem organ involvement, laboratory evidence of inflammation, and laboratory or epidemiological evidence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, in individuals aged 0–19 years with no alternative diagnosis. Neurological manifestations are not part of the diagnostic criteria of MISC and hence remain poorly described. So, we wanted to note down the neurological involvement in multisystem inflammatory syndrome in children (MIS-C) related to severe acute respiratory syndrome with coronavirus infection. Here we describe 6 cases of COVID MISC who presented as acute febrile illness with drowsiness, irritability, convulsions and serious ones with encephalopathy. Focal neurological signs, abnormal brain magnetic resonance imaging (MRI) was present in four patients. MRI brain was normal in 2 cases CSF study was normal in all cases. These patients received intravenous methylprednisolone at 30 mg/kg/day for 3 days. Cases 3 to 6 were given intravenous immunoglobulin (IVIG), the clinical picture rapidly improved in the first three days, and all neurological symptoms disappeared within 10 and 30 days with some sequel in cases 4 to 6. In conclusion we describe clinical and laboratory parameters in these patients with neurological manifestations and we documented an increase in pro inflammatory markers correlating with severity of neurological presentation in children with MISC. High index of suspicion is needed to diagnose neurological manifestations of MISC following COVID-19 pandemic. Neurological spectrum can be broad range of manifestations though outcome was favorable with early treatment.